(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Scholar, critic, and methodologist of great insight — Qozoqboy Yo’ldosh’s literary-critical perspectives stand apart from those of his contemporaries due to their analytical coherence and firm grounding in scholarly evidence. In this article, we attempt to explore Yo’ldosh’s literary and critical outlook by examining how he employs a cultural-historical approach in the study of selected writers and their creative works